Programmable droplet microfluidics for complex multistep bioassays - Enqi Huang; Yu Wang; Dongyang Cai; Dayu Liu (Interdisciplinary Medicine, 2024)
Abstract Programmable droplet microfluidics (PDM) refers to a microfluidic device that integrates the functionality of a series of droplets with distinct spatial locations in a designated temporal order. PDM streamlines the intricate workflow of complex bioassays by enabling programmable and macroscopic droplet displacements, in which the droplets serve as reservoirs for reagents, microvalves for liquid insulation, and in some cases micropumps for mass transportation. As these droplets are intangible structures, the need for expensive microfabrication procedures is eliminated. Furthermore, the parallelization of the droplet series provides flexibility in controlling the throughput of the microfluidic analysis system. This paper provides a comprehensive review of PDMs enabled by various microfluidic mechanisms, including magnetism actuation, relative liquid displacement, capillary suction and sequential microdisplacement. Additionally, important applications of PDM systems for nucleic acid detection, immunoassay, drug testing, and sample recovery are also introduced. In conclusion, PDM demonstrates its potential as a highly advantageous tool for executing intricate multistep bioassays on a microfluidic platform. These technologies have exhibited superiority over their traditional counterparts in terms of size reduction, automation, and low sample/reagent consumption.